Cueing Morality: The Effect of High-Pitched Music on Healthy Choice - Huang, Xun (Irene); Labroo, Aparna A. (Journal of Marketing, 2020)
Managers often use music as a marketing tool. For example, in advertising, they use music to intensify emotions; in service settings, they use slow music to boost relaxation and classical music to convey sophistication. In this article, the authors posit a novel effect—higher-pitched music can boost healthier choices. Recognizing that many perceptual characteristics of higher pitch (e.g., lighter, elevated) are conceptually associated with morality, they theorize that listening to higher- (vs. lower-) pitched music can cue morality. Furthermore, thoughts about morality can prompt moral self-perceptions and, in turn, thoughts about “good” behaviors, including healthy choices. Thus, listening to higher-pitched music may increase healthier choices. Employing field settings and online studies, the authors find that listening to higher-pitched music increases consumers’ likelihood to choose healthy options (Studies 1, 3, and 5), choose lower-calorie foods (Study 2), and engage in health-boosting activities (Study 4). This effect arises because high pitch raises the salience of morality thoughts (Studies 4 and 5). The article concludes with a discussion of theoretical and managerial implications.